Influence of School Environment on Senior Secondary School History Students’ Academic Performance in In Jos South Lga of Plateau State, Nigeria - Shittu Lukman Olayinka; Muhammad Ridwan (Matondang Journal, 2025)
This study investigated influence of school environment on senior secondary school history students’ academic performance in in Jos south LGA of Plateau State, Nigeria. The study formulated one aim and four specific objectives. In line with these objectives the study raised and answered four corresponding research questions. Two null hypotheses were also tested at 0.05 level of significance. Extensive literature was reviewed concerning the variables and issues in the study. Empirical studies were also reviewed and gaps in literature were identified. The study adopted a survey research design specifically cross-sectional survey research design. The study population consisted of 521 SS II history students across the 20 public schools in Jos South LGA for 2025 academic year. From the population a sample of 100 students were selected from 10 schools using simple random sampling technique. To generate data for the study the researcher used a structured questionnaire also referred to as close ended questionnaire. The questionnaire was titled Influence of school environment on academic performance of SS II History students in in Jos South” (ISEAPSH). Content validity was established by experts and reliability was determine at 0.71 using Cronbach Alpha method for internal consistency. Direct method of data collection was established and data collected was analysed using descriptive and inferential statistics. The findings revealed among other things that, types of Learning Environments Available: The study identified that students have access to varying forms of learning environments, which include physical infrastructure, classroom size, access to educational resources like libraries and ICT tools, and teacher-student interactions among others. The study concluded that school environment has significant influence on academic performance of History students in Jos South LGA. The study recommended among other things that, government and school proprietors should invest in classroom infrastructure, ensuring adequate space, proper seating, ventilation, and lighting.